The role of the state in contemporary processes of late-late development. A diagnosis of the Ethiopian experience to illustrate a renewed debate - Pérez-Lagüela, Elena (Iberoamerican Journal of Development Studies, 2024)
Recent economic performance in Ethiopia has revived research on the role of the state in development processes. Assessing the relevance of the Ethiopian experience provides valuable insights to the discussion on the scope and limits of state action in other contemporary development experiences. This paper presents a case study based on elite interviews conducted during fieldwork in Ethiopia. The results of our research suggest that, while it is possible to argue that the Ethiopian state acquired developmentalist traits during the period 1994-2015, the characterisation of the state as «developmentalist» was used to sustain Meles Zenawi’s personalist political project. In Ethiopia, state-led development was not just an economic strategy aimed at structural transformation, but rather a means to maintain power.